Analysis Of Factors Affecting Income Inequality Between District Areas In Dumai City - Nurasriani Nurasriani; Misdawita Misdawita; Yelly Zamaya (Dinasti Publisher, 2025)
Simon Kuznet explained the inverted U curve theory regarding inequality, which said that as a country develops, inequality will increase until it reaches a certain critical point, and after that inequality will begin to decrease. So this research is aimed at finding out the extent of income inequality between sub-district areas in Dumai City and analyzing things that have the potential to cause this inequality, using secondary data from 5 sub-districts in Dumai City from 2015 to 2023. All data provided used was obtained from the Basan Statistics Center of Dumai City and then processed using PSPP software. Analysis of inequality using the Williamson Index and fixed effect model panel data regression, resulted in the independent variables, namely agricultural productivity, road stability, economic growth and population growth rate, each having a significant effect on income inequality between sub-districts in Kot Dumai.